1988
DOI: 10.1016/0022-0248(88)90094-2
|View full text |Cite
|
Sign up to set email alerts
|

Crystal growth and characterization of Ce1-xPrxO2 (x≃0.05) single crystals

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…The compositions Ce 0.95 Zr 0.02 Pr 0.03 O 2 and Ce 0.95 Sn 0.02 Pr 0.03 O 2 exhibits better L * , a * , and b * values (47.63, 22.60, and 22.08) and (54.65, 22.35, and 23.26), respectively. It is clear from the L * a * b * values of the Ce 0.95 Zr x Pr 0.05− x O 2 and Ce 0.95 Sn x Pr 0.05− x O 2 pigments summarized in Tables I and II that the present values are significantly higher than the recently reported praseodymium‐doped ceria powders (5% praseodymium‐doped CeO 2 : L * =66; a * =12; b * =9.5), synthesized by a microwave‐assisted hydrothermal route 18 . Nahum et al 22 have reported similar color properties as found in the present study with Pr 4+ ‐doped ceria pigments calcined at 1400°–1500°C.…”
Section: Resultsmentioning
confidence: 48%
See 1 more Smart Citation
“…The compositions Ce 0.95 Zr 0.02 Pr 0.03 O 2 and Ce 0.95 Sn 0.02 Pr 0.03 O 2 exhibits better L * , a * , and b * values (47.63, 22.60, and 22.08) and (54.65, 22.35, and 23.26), respectively. It is clear from the L * a * b * values of the Ce 0.95 Zr x Pr 0.05− x O 2 and Ce 0.95 Sn x Pr 0.05− x O 2 pigments summarized in Tables I and II that the present values are significantly higher than the recently reported praseodymium‐doped ceria powders (5% praseodymium‐doped CeO 2 : L * =66; a * =12; b * =9.5), synthesized by a microwave‐assisted hydrothermal route 18 . Nahum et al 22 have reported similar color properties as found in the present study with Pr 4+ ‐doped ceria pigments calcined at 1400°–1500°C.…”
Section: Resultsmentioning
confidence: 48%
“…CeO 2 is a fluorite‐structured oxide that can form extensive solid solutions with a variety of alien cations while retaining the fluorite crystal structure. Praseodymium‐doped CeO 2 ceramic pigments are interesting because they produce colors ranging from brick red to dark brown, depending on the quantity of praseodymium, synthesis conditions, and the calcination conditions 18–22 . The substitution of other lanthanides such as La, Sm, Nd, and Gd in CeO 2 –PrO 2 have also been investigated and yielded various hues ranging from pink‐orange to yellow 23,24 .…”
Section: Introductionmentioning
confidence: 99%
“…have been reported with a red hue. [27][28][29][30][31] Disadvantages of such methods could be those relating to cost, need for high calcination temperatures, release of toxic gases, etc.…”
Section: Introductionmentioning
confidence: 99%
“…coprecipitation of hydroxides, oxalates or carbonates, urea homogeneous coprecipitation, flux method, combustion, pirolysis, hydrothermal or microwaveassisted hydrothermal, and so forth). 1,2,5,21,33,[35][36][37][38][39][40][41] Noteworthy, previous investigations have demonstrated that ceramic pigments based on Tb-CeO 2 solid solutions may also yield good red hues, 20,21,42,43 which may be comparable to those obtained with Pr-CeO 2 . Nevertheless, the studies about synthesis optimization and pigmenting properties of Tb-doped ceria are still rather scarce, since most of research concerning this system is centred on catalytic or redox properties.…”
Section: Introductionmentioning
confidence: 79%